Otosclerosis in an Urban Population. Issue 1 (January 2021) - Choi, Jonathan S.; Sweeney, Alex D.; Alava, Ibrahim; Lovin, Benjamin D.; Lindquist, Nathan R.; Appelbaum, Eric N.; Vrabec, Jeffrey T.
Abstract : Objective: To investigate the evolving prevalence of otosclerosis in a large urban population. Methods: A retrospective review of patients in a large, urban, public health system was conducted from January 2010 to August 2019 to identify subjects with otosclerosis. Diagnostic testing included audiometry and computed tomography scans. Sex, age at diagnosis, treatment received, race, ethnicity, and country of birth were analyzed for each subject and compared with all eligible patients in the reference population. Results: A total of 134 patients from a reference population of 672, 839 were diagnosed with otosclerosis and analyzed. The otosclerosis patients were predominantly Hispanic (73%), of which the majority were foreign born (87%). The average age at onset was 46 years and 59% were women. The overall prevalence of otosclerosis was 20 of 100, 000 patients. The crude prevalence of otosclerosis by ethnicity was 43 of 100, 000 for Hispanics, 12.6 of 100, 000 for Caucasians, and 3 of 100, 000 for African Americans. Within the Hispanic population, the prevalence of otosclerosis was 60 of 100, 000 for foreign-born individuals and 16 of 100, 000 for those born in the USA (odds ratio [OR] = 3.69, [95% confidence interval [CI], 2.02–6.76], p < 0.0001). Prevalence was not significantly different among Caucasians and US-born Hispanics. Conclusion: Otosclerosis in the studied population was most common among Hispanic patients, though it was strongly influenced by country of birth. The "imported" otosclerosis cases are best explained by environmental influence rather than ethnic susceptibility. This discrepancy is likely due to variance in measles immunization rates among North and Central American countries before 1990.